Competitiveness through cooperation: Analysis of spatial patterns and inter-jurisdictional collaboration in the place branding of Ontario communities, Canada. (June 2014) - Cleave, Evan; Arku, Godwin
Place branding is an important tool of economic development, underpinned by neoliberal policy and the processes of global competitiveness as communities at all geographic scales are becoming the primary nexus for economic development, and are forced to compete with one another for finite resources, direct investment, talent and immigrants, and tourism. Within the framework of global competition, it is often argued that communities can undertake inter-jurisdictional cooperation to enhance their competitiveness. To this end, this paper attempts to fill a gap in place branding literature by examining whether there are clusters of communities that currently have the potential to cooperate in their branding efforts. This research uses spatial autocorrelation of place brands amongst the communities of Ontario, Canada, to identify potential global patterns in branding and groups of neighbouring communities with similar brand messages. The results of this analysis show that Ontario has the potential for as many as 20 clusters in a variety of economic sectors. The existence of these clusters, therefore, provides a template for future place branding policy development within the province, allowing the participating communities an opportunity to remain relevant against global competitors.